Digitalization in the single transport space of the EAEU - A. M. Novozhilov (Путеводитель предпринимателя)
The phenomenon of digitalization contributes to the implementation of the strategic national goals of states and international associations. The members of the Eurasian Economic Union form a single digital space of the EAEU, implement the processes of digitalization, digital logistics, the development of intelligent transport systems, and the introduction of electronic transport documents.